Identifying Institutions and Strategic Programs to Increase Sugarcane Production in Southeast Sulawesi, Indonesia - Sulaiman, Andi Amran; Arsyad, Muhammad; Rahmatullah, Rio Akbar; Ridwan, Muhammad (Caraka Tani: Journal of Sustainable Agriculture, 2023)
The decline in the productivity of the national sugarcane commodity has become an issue in the last ten years. When domestic demand for sugar is increasing, the decline in productivity indicates a crisis in sugarcane production. At the same time, the involved institutions and strategic programs to encourage sugarcane production have not been well identified. The research aims to determine the institutions that are expected to play a role and the strategic programs that are prioritized in increasing sugarcane production in Southeast Sulawesi, Indonesia. This study uses Interpretative Structural Modeling (ISM) to formulate complexity, hierarchy (levels) and classification among elements. The results showed that of the 14 sub-elements of the acting institutions studied, five institutions were key actors for increasing production, namely banking institutions; universities; agricultural, plantation and fisheries offices; industry, trade, cooperatives, & Small and Medium Enterprises (SMEs') offices; and private companies. Then, from the 13 sub-elements of the strategic programs, there are five strategic programs that also serve as the key programs, namely extension/assisting farmers; addition of plantation labor; providing access to capital; variations of profit-sharing and buying systems of sugarcane; and accuracy of time and adequacy of the supply of raw materials to the mills. This means that these institutions must play an important role, as well as strategic programs that must be carried out effectively to address the issue of sugarcane production in the country. Thus, researchers recommend involving all stakeholders in conducting strategic programs with the key actors as the leading driving institutions.